Feuding Families: When Conflict Does a Family Firm Good - Kellermanns, Franz W.; Eddleston, Kimberly A. (Entrepreneurship Theory and Practice, 2004)
Using the conflict theory lens and insights from the family business literature, we develop a theoretical model concerning the effects of task, process, and relationship conflict in family firms. Family firms are characterized by different control structures and generational involvement. Accordingly, we discuss the expected effect control concentration has on task, process, and relationship conflict, and propose that generational involvement affects the importance of task and process conflict to a family firm's performance. Furthermore, our model suggests that relationship conflict moderates the outcomes of task and process conflict. The degree of relationship conflict in family firms is in turn influenced by altruism, which characterizes interactions among family members.